Lazer no preto e branco: histórias de integração do negro pelo lazer e animação sociocultural voluntária no Clube Palmares em Volta Redonda - RJ - Oliveira, Carlos Gomes de (2012)
This study developed at the Post Graduation Program in Education Associated in PE, physical education-UEM/UEL in practice lines, politics and knowledge production in Physical Education, covers the issue from the point of leisure and aid in memory retrieval of Club Palmares, which was created in 1964 to be a space of inclusion of african descendent in entertainment, in Volta Redonda, Rio de Janeiro. The club was founded as a refusal from the system which did not accept them in the social clubs of the city, in a time of racism less nuanced. The goal of this paper is to investigate the memory of Palmares Club, and understand its importance in racial integration and promotion of cultural practices related to the body, with a view at the political, social, economic, besides developing an intervention through the possibilities and limits of the sociocultural context of the club with the objective of training new leaders for the perpetuation of its name. Making this material available so that it can assist in new research projects that seek an approach to the problem of the foundations of leisure in african descendant social clubs in an attempt to strive for a balance between understanding the theory and practice of systematized leisure activities, serving the needs of population in general. The research subjects are members and dependents of Palmares Club and they also participate in the line of movement. The historical data collection occurred through oral sources, it occured the interview of seven people who participate actively in the club. The work was supplemented by documents as photos, blogs and newspaper clippings. It was made an african descendent survey related to their history and some of the major events involving the club during its period of glory struggles achieved by strategies and awareness and about the real importance of these people to the development of the country. Through diagnostic actions during the visits to the Palmares Club, it became clear that the leaders have a great knowledge about the reality of the community. There is a hierarchy of authority and respect from its members towards the founding partners, the dialogue between them are very fluent and easy which promotes the circulation of hypotheses that need to be discussed. The strategy of social and cultural animation activities of the club to perform a dynamic reflective intervention aimed at the collective work with a lot of planning. The youth club started to act more actively due to initiatives focusing on (ASC).